Synthesis and Characterization of Thorium(IV) and Dioxouramum(VI) Complexes of a Schiff Base: Part 1. - R. KHAN, A.; SHARMA, K.P.; ARORA, KISHOR (Asian Journal of Chemistry, 2010)
A new series of Th(IV) and UO2(VI) with a Schiff base derived from condensation of m-methyl aniline and p-(N,N'-dicyanoethyl) amino benzaldehyde having general composition ThX4·nL (X = NO3-, n = 2; X = NCS-, n = 2 : X = I-, n = 4; X = CIO4- , n = 6); and UO2X2·2L (X = NO3-, I-, NCS- or CH3COO- ) and UO2(CIO4)2·4L where L is the Schiff base. The complexes were characterized on the basis of analytical conductance molecular weight and spectral studies. The Schiff base behaves as a neutral monodentate ligand which coordinates to the central metal atom through azomethine nitrogen.